The Alaska Highway Development - Bucksar, Richard G. (ARCTIC, 1974)
Thirty-one years ago, in November of 1942, the Alaska Highway was opened for use as a military road. Built as a long-range defense measure, it was assumed that improvements would continue following World War II. Since that time, there have been many proposals to pave the road, but they have been blocked by political and economic considerations. The resulting highway had a good gravelled driving surface, but was rough and uneven. After the responsibility for the highway was transferred from the United States Army to the Royal Canadian Engineers, the terms of reference under which operations were carried out did not permit major road relocations. . the alignment of the highway is essentially the same today as it was in 1943. The highway is Alaska's only land link with the lower forty-eight States and a major road serving the Yukon, yet of the nearly 1,525 miles of road, to date less than 400 miles are paved. The remaining 1,100 odd miles are at best a dusty and difficult ordeal . With both United States and Canadian interest increasing toward the growth and development of the northwest, there can be little doubt that a paved road would be of substantial value to both countries. The present reaction to the issue of paving is somewhat a mirror of past negotiations. The federal governments of the United States and Canada are cool toward the issue, while local interest in both Alaska and the Yukon is quite high. . Measures to improve the Alaska Highway have been periodically brought before the Canadian Parliament and the United States Congress, but a growing disparity of interests beginning in the 1950s, has made negotiations very difficult. . The disparity in population and power between Canada and the United States has understandably created a defensive reaction on the part of Canadians which takes the form of sensitivity to any real or fancied slight to Canadian sovereignty. . both countries now feel that the Canadian portion of the road would be better administered by Canada. Numerous bills were sponsored during ...